Teks Geguritan Prasada Niti Analisis Struktur, Fungsi, dan Makna - Tri Irmayuni, Ni Komang; Rai Putra, Ida Bagus; Suryati, Ni Made (Humanis, 2016)
This study examines the text Geguritan Prasada Niti. The purpose of this study to describe the structure , function , and meaning contained in the text Geguritan Prasada Niti. The theory used in this research is the structural theory and the theory of functions according to Luxemburg and semiotic according to Pierce . The methods and techniques used are divided into three stages, namely (1) the stage of providing data use  observation methods with transliteration techniques, technique of recording and translation techniques, (2) the stage of data analysis using qualitative methods with techniques descriptive analytic, (3) stages presentation of data analysis using formal and informal methods with inductive - deductive techniques. The results obtained in this study is a structure consisting of structures forma and content structure. Structure forma; (1) pupuh / padalingsa; smarandana puh, ginanti puh, dandang gendis puh, mijil puh, and  pucung puh, (2) a variety of language; Bali Alus language, (3) language style; style stylistic comparisons and stylistic contradictions. Content structure ; (1) the first part ; begins with mantras, (2) part of an early transition to the contents ; an early introduction to enter the contents, (3) part of the contents; contains the teachings of leadership, (4) the content to the end of the transition section; an introductory statement that the work has been completed (5) the final part; a statement that the work of the authors has been completed. In addition there is a function that consists of ethical teaching function and the function of self-control and there is a meaning which consists of the meaning of well-being and the meaning of love.